Correlation Between the Level of Reliability and Ethics with the Perception of the Effectiveness of AI Use in Scientific Paper Writing by Students - Febrianti, Lifia Yola (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
In the practice of writing scientific papers, students utilize AI for various purposes that assist and facilitate the process. This study aims to determine the correlation between reliability and ethics with the perception of the effectiveness of AI use in scientific writing by students. The method used in this study is quantitative with a correlational research type. The data collection techniques in this study are observation and survey with questionnaire distribution. The questionnaire used Google Forms and was distributed to 50 students who participated in scientific writing training in high school. Data analysis included normality tests, linearity tests, and correlation tests. The data analysis method used in this study was correlational analysis to determine the relationship between variables using product moment analysis with SPSS 23. The results showed that there was a relationship between the level of AI reliability (X1) and the perception of the effectiveness of AI use in students' scientific writing (Y) with a correlation value of 0.726. Similarly, the AI ethics variable (X2) showed a fairly high correlation with the perception of effectiveness (Y) of 0.696. Both correlation values are in the strong correlation category (0.70–0.90), indicating that the higher the reliability and ethics of AI perceived by students, the higher their perception of the effectiveness of AI use in scientific writing.